2021
DOI: 10.7759/cureus.14948
|View full text |Cite
|
Sign up to set email alerts
|

A Curious Case of Acute Acalculous Cholecystitis

Abstract: Acute acalculous cholecystitis is inflammation of the gallbladder without any evidence of gallstones. Although acalculous cholecystitis is less common than its calculous counterpart, it can be fatal if not treated. It is essential to rule out the cause of acalculous cholecystitis to aid in the treatment and management of the patient. We present a case of acalculous cholecystitis wherein a comprehensive workup found the etiology to be viral. Albeit rare, hepatitis A and cytomegalovirus can be causes of acute ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…12,14,41 HAV-induced AAC is rare with only 29 reports from 1992 to 2022 consisted of a total 71 patients in the literature; of these patients, 44 (61.9%) were under 18 years old and 27 (31.8%) were over 18 years old (Table 3). The incidence of HAV-induced AAC in the adult population is less than pediatrics, and it is mostly seen in the developing and endemic areas of HAV; 22,45 We found that the youngest patient was 2.5-year-old and the most elderly was 81-year-old. 46,47 HAV-induced AAC can lead to gallbladder perforation, cholangitis, pleural effusion, ascites, acute pancreatitis, and co-infection with various microorganisms.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…12,14,41 HAV-induced AAC is rare with only 29 reports from 1992 to 2022 consisted of a total 71 patients in the literature; of these patients, 44 (61.9%) were under 18 years old and 27 (31.8%) were over 18 years old (Table 3). The incidence of HAV-induced AAC in the adult population is less than pediatrics, and it is mostly seen in the developing and endemic areas of HAV; 22,45 We found that the youngest patient was 2.5-year-old and the most elderly was 81-year-old. 46,47 HAV-induced AAC can lead to gallbladder perforation, cholangitis, pleural effusion, ascites, acute pancreatitis, and co-infection with various microorganisms.…”
Section: Discussionmentioning
confidence: 71%
“…AAC was first reported in 1844 by Duncan J in a fatal case of AAC complicating an incarcerated hernia. 21 In fact, AAC is a type of acute cholecystitis which constitutes 5 -10% of all acute cholecystitis without presence of gallstones, 19,22 which occurs in the setting of gallbladder dysfunction and often occurs in criticallyill patients in the ICU. 19 AAC is a life-threatening state in which the critical complications include necrosis and perforation of the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 45 The initial AAC diagnosis is made clinically, which is confirmed with the help of abdominal ultrasound. 27 The five main ultrasonographic diagnostic criteria of AAC are 1. gallbladder distention; 2. gallbladder wall thickening greater than 3.5 mm; 3. absence of stone (no acoustic shadow) or sludge in the gallbladder; 4. perivesical liquid collection; and 5. absence of intra‐ and extrahepatic bile duct dilatation with a sensitivity, specificity, and accuracy of 88.9%, 97.8%, and 96.1%, respectively. 45 , 46 Most AAC patients are candidates for percutaneous cholecystostomy, a definitive treatment option with a low mortality rate and following cholecystectomy (except in patients with gallbladder perforation or gangrene).…”
Section: Discussionmentioning
confidence: 99%